Inherited prion disease with A117V mutation of the prion protein gene: a novel Hungarian family. Issue 6 (1st June 2001) - Kovács, G G; Ertsey, C; Majtényi, C; Jelencsik, I; László, L; Flicker, H; Strain, L; Szirmai, I; Budka, H
Abstract : Three members of a family with inherited prion disease are reported. One additional family member had a progressive neurological disease without details. Two developed symptoms of ataxia, dementia, myoclonus, rigidity, and hemiparesis, and one had a different phenotype with the combination of lower motor neuron deficit, parkinsonism, intellectual decline, and ataxia. In this last patient cell loss of the anterior horn motor neurons and chronic neurogenic muscle atrophy was evident. Immunostaining for the prion protein disclosed unicentric and multicentric plaques, and coarse and fine granular positivity. Genetic analysis of the prion protein gene of the propositus showed a 117 codon alanine to valine mutation and homozygous 129 valine/valine genotype.